2018
DOI: 10.4103/psychiatry.indianjpsychiatry_153_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the extent of utilization of biopsychosocial model in doctor–patient interaction in public sector hospitals of a developing country

Abstract: Background:Biopsychosocial (BPS) model has been a mainstay in the ideal practice of modern medicine. It is attributed to improve patient care, compliance, and satisfaction and to reduce doctor–patient conflict. The study aimed to understand the importance given to BPS model while conducting routine doctor–patient interactions in public sector hospitals of a developing country where health resources are limited. The study was conducted in Rawalpindi, Pakistan.Materials and Methods:The study design is qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…On the other hand, avoidance/delay in seeking treatment has been related to dislike or distrust in practitioners and general dislike of medical treatment,29 while greater adherence to treatment is related to clinicians who provide clear information, emotional support and empathy, and treat patients as partners in the process 30 31. Despite the benefits of such a model of physician–patient partnership, within some contexts (especially non-Western Educated Industrialised Rich and Democratic, that is, non-WEIRD), adherence is positively related to obedience and treatment satisfaction 32 33. This suggests that, in certain contexts, patients’ passivity is normalised or even expected, thus making the relation with adherence less clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, avoidance/delay in seeking treatment has been related to dislike or distrust in practitioners and general dislike of medical treatment,29 while greater adherence to treatment is related to clinicians who provide clear information, emotional support and empathy, and treat patients as partners in the process 30 31. Despite the benefits of such a model of physician–patient partnership, within some contexts (especially non-Western Educated Industrialised Rich and Democratic, that is, non-WEIRD), adherence is positively related to obedience and treatment satisfaction 32 33. This suggests that, in certain contexts, patients’ passivity is normalised or even expected, thus making the relation with adherence less clear.…”
Section: Introductionmentioning
confidence: 99%
“… 30 31 Despite the benefits of such a model of physician–patient partnership, within some contexts (especially non-Western Educated Industrialised Rich and Democratic, that is, non-WEIRD), adherence is positively related to obedience and treatment satisfaction. 32 33 This suggests that, in certain contexts, patients’ passivity is normalised or even expected, thus making the relation with adherence less clear. Furthermore, adherence is consistently related to patients’ trust in the healthcare system and healthcare providers: trusting patients are more likely to adhere to treatment and follow public health recommendations (see Chandra et al 34 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Most had a mixed-methods approach and limited articles had a purely qualitative methods. [ 13 14 15 16 17 ] Similarly, the papers presented at ANCIPS had few researches using qualitative methodology (1.3%). Analyzing further, it was found that the published articles and conference abstracts showed a rising trend when those from the second half of the decade are compared with the first half.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, there is great concern about the lack of support for mental health in patients suffering from CLD [6], and their quality of life [7]. In Pakistan speci cally, there is even greater concern as mental health is not a priority area for the health sector [8], and the 'bio-psycho-social-spiritual model' [9] which is important to secure the quality of life in patients is less understood or integrated in the health system [10]. It is thus that patients holistic care with regard to integrated and multidimensional care including clinical attention, social support, and spiritual wellbeing are less considered.…”
Section: Introductionmentioning
confidence: 99%